Social media influence on destination choice: A study among students of University Malaysia Kelantan (UMK) - Mazlan Radzwan; Muhammad Aslam Mohamed Hasan Farook; Nadirah Mohd Pera’aid; Usamah Sahrudin (2021)
Social media are interactive technologies that enable people to create, share and exchange content, thoughts and other modes of expression through virtual communities and networks. Any multimedia medium that helps users to easily build and post content with the public is referred to as social media. The term “social media” refers to a variety of websites and applications. The aim of this research is to investigate the social media influence on destination choice among students of University Malaysia Kelantan. Specifically, this study investigated what is the relationship between the independent variables which are the usage habit of social media, types of social media usage, the usefulness of social media usage, tourist attitude and destination choice which was the dependent variable. The researchers also want to identify the relationship between the usage habit of social media, types of social media usage, the usefulness of social media usage and also tourist attitude towards destination choice among youth in Universiti Malaysia Kelantan Kampus Kota. The researchers selected the sample of at least 330 students of Universiti Malaysia Kelantan Kampus Kota. Data collected using a questionnaire and analyse through descriptive analysis, reliability test and Pearson’s Correlation Coefficient. As a result, the researchers understand the function of social media that provided benefits and convenience for tourist which rely on social media when travelling. From the results, the researchers can conclude that usage habit of social media is the highest significant which is 0.858 that influences destination choice of youth using social media and the lowest on is usefulness of social media usage, 0.676 which influences destination choice among youth using social media. Other ideas should be used as reference for future studies in order to learn more about the variables that influence destination choice among young people using social media.